CONGRATULATIONS TO THREE USM STUDENTS, PROUD RECIPIENTS OF YANG DIPERTUAN AGONG SCHOLARSHIP 2017 - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
KUALA LUMPUR, 24 May 2017 – The Yang diPertuan Agong, Sultan Muhammad V has awarded the Yang Dipertuan Agong Scholarship (BYDPA) 2017 to 12 students from higher educational institutions here at Istana Negara.